Screening of Phytochemical Studies of Honey (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
The process of phytochemical screening is used to find active ingredients in honey that may have antibacterial and antioxidant properties. By qualitatively testing for alkaloids, steroids, flavonoids, and quinones, this study intends to ascertain the phytochemical content of three varieties of monofloral honey from Java (kapok, rubber, and mango honey) and four varieties of multifloral honey from Summava. Three types of monofloral and multifloral honey were positively identified as having flavonoids and saponins based on the results of phytochemical screening. These substances have antioxidant and antibacterial properties and are secondary metabolic substances.